2005
DOI: 10.1111/j.1570-7458.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Host color preferences and short‐range searching behavior of the egg parasitoid Trichogramma ostriniae

Abstract: The color of lepidopteran eggs often varies by species or egg condition, and parasitoids that attack lepidopteran eggs could therefore potentially use color to obtain information about host identity or quality. The objective of our study was to determine whether females of the egg parasitoid Trichogramma ostriniae Pang & Chen (Hymenoptera: Trichogrammatidae) showed differential responses to egg color when searching for hosts over short distances and when evaluating the suitability of encountered eggs. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…For egg parasitoids there is less information related to the use of colours during host searching with the exception of some studies on Trichogramma spp. (Romeis et al, 1998;Lobdell et al, 2005) and for the egg parasitoid Ooencyrtus kuwanai (Howard) (Weseloh, 1972).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For egg parasitoids there is less information related to the use of colours during host searching with the exception of some studies on Trichogramma spp. (Romeis et al, 1998;Lobdell et al, 2005) and for the egg parasitoid Ooencyrtus kuwanai (Howard) (Weseloh, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Many phytophagous insects have a preference for particular structures of plants to feed or lay eggs (Udayagiri & Welter, 2000;Blackmer et al, 2001); these structures can be told apart by the parasitoids based on colour, allowing them to select (micro) habitats when foraging. The colour of the host can also help the parasitoids in recognition and in gathering information about host quality (Lobdell et al, 2005). In addition, parasitoids could use colours when foraging for food, to guide themselves towards flowers to find nectar, or other food resources (Wäckers, 1994) Host-searching behaviour of parasitoids is influenced by innate behaviour, experience, and associative learning (Vinson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The preference for the colour yellow we found in F. arisanus has been reported for other hymenopterans, including egg parasitoids (Lobdell et al 2005). In the case of fruit fly parasitoids, Diachasmimorpha juglandis (Muesebeck) chose yellow walnut fruits over black fruits despite that the latter are more likely to contain host larvae (Henneman 1998).…”
Section: Discussionmentioning
confidence: 68%
“…Parasitoids' color ! 7 preference, however, could be linked to information regarding hosts' identity, developmental stage, substrate, or previous parasitization (Lobdell et al, 2005). In addition, parasitoids' behavior towards stimuli is affected by mechanical cues that evoke further responses.…”
Section: Visual Cuesmentioning
confidence: 99%
“…Lobdell et al (2005) indicated that the egg parasitoid, Trichogramma ostriniae, using color as a visual cue, has the potential to control the density of the lepidopteran Ostrinia nubilalis in maize fields. The parasitoid's behavior towards yellow, black, white, and green beads representing the eggs was analyzed using a Petri dish arena with green background.…”
Section: Visual Cuesmentioning
confidence: 99%